93. Phosphorylated α-synuclein biomarker in skin nerves is differently expressed in pure autonomic failure and idiopathic Parkinson disease. Issue 4 (April 2016) - Donadio, V.; Incensi, A.; Piccinini, C.; Cortelli, P.; Giannoccaro, M.P.; Baruzzi, A.; Liguori, R.
Abstract : The aim of this study was to characterize the expression in skin nerves of native (n-syn) and misfolded or phosphorylated (p-syn) α-synucleins in pure autonomic failure (PAF) and idiopathic Parkinson disease (IPD). We studied 30 patients, including 16 well-characterized IPD, 14 patients fulfilling PAF diagnostic criteria, and 15 age-matched controls. Subjects underwent skin biopsy from cervical, thigh and leg sites to study small nerve fibers and intraneural n-syn and p-syn. PAF and IPD both showed a skin denervation, more severely expressed in patients with higher p-syn load. N-syn was similarly expressed in both groups of patients and controls. By contrast, p-syn was not found in controls, but it was disclosed in all PAF and IPD patients with different skin innervation. In addition, abnormal α-syn deposits were found in all analysed skin samples in PAF, but in 49% of samples only with higher positivity rate in the cervical site in IPD. In conclusion: (1) intraneural p-syn was a reliable in vivo marker of PAF and IPD; (2) neuritic p-syn inclusions differed in PAF and IPD, suggesting a different underlying pathogenesis; (3) searching for abnormal p-syn deposits in skin nerves, the site of analysis is irrelevant in PAF, but it is critical in IPD.